(untitled) (Ushuluddin International Conference (USICON), 2019)
Robotics technology continues to develop the latest developments as happened in 2016, Hong Kong Hanson Robotics activates the Social Humanoid Robot named Sophia. This robot has the appearance and behavior like humans who can dialogue, move, and express. This humanoid robot technology continues to be developed so that intelligence, response abilities, and social skills are increasingly increasing. In the future, the development of the quality and quantity of these humanoid robots can be a threat to humans in the social environment. Robotic abilities that are more reliable can shift the role of humans. However, in the Koran it is explained that humans have been created in the best form and carry out the task as a caliph on earth. Therefore, humans must try so that he does not lose in the midst of the development of sophisticated robot technology. This research seeks to examine what are the special abilities of humans as prescribed in the Qur’an. The goal is for humans to know and maximize human features so that they still exist despite the ability of increasingly sophisticated robots that can match, even rival human abilities. This research was conducted by conducting a library research (library research) on the content of the content in depth in the Qur’an. This study collects verses of the Qur’an and supporting traditions to analyze phenomena in the contemporary era. From this research, it was obtained that in the Koran it was mentioned that humans were moral beings as mentioned in Surah al-Qalam verse 4. In addition, in Surah Al-’Imran verse 159 also explained the gentle behavior towards others humans are difficult to equate with the performance of robots mechanically and procedurally. By maximally internalizing the two messages in the Qur’an, humans are able to stay ahead in the social environment because they have piety and faith as a guide for life even though humanoid robot technology continues to be developed.